2021
DOI: 10.21203/rs.3.rs-779813/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Transcriptome Profile Reveals The Regulatory Mechanism of Verticillium Dahliae Against Bacillus

Abstract: Background: Verticillium dahliae, the causal agent of Verticillium wilt, is notoriously invasive in many crops and has been involved in numerous epidemics worldwide. Bacillus species, as representatives of biocontrol bacteria, produce a variety of lipopeptides (LPs), which are useful as biofungicides to many pathogenic fungi, including Verticillium dahliae. This study will explore the mechanism of resistance of V. dahliae to Bacillus and biocontrol bacteria.Results: By using in vitro confrontation bioassays, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 77 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Thus far, there are several transcriptome studies of plant pathogenic fungi incubated with Bacillus species or their crude culture filtrates. For example, RNA was analyzed from Colletotrichum gloeosporioides TS-09 grown on PDA with B. amyloliquefaciens SDF-005 for 9 days [ 39 ], Verticillium dahliae VdSHZ-9 grown on PDA with Bacillus N-4 for 7 days [ 40 ], and Fusarium oxysporum grown on PDA with B. subtilis HSY21 for 2 and 3 days [ 29 ]. RNA was also analyzed for Sclerotinia sclerotiorum 1980 grown on PDA containing 10% culture filtrate of B. amyloliquefaciens Bam22 for 1 day [ 41 ], and Botrytis cinerea strain B05.10 grown in PDB with B. subtilis MBI 600 culture filtrate for 0, 24, 48, and 72 h [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus far, there are several transcriptome studies of plant pathogenic fungi incubated with Bacillus species or their crude culture filtrates. For example, RNA was analyzed from Colletotrichum gloeosporioides TS-09 grown on PDA with B. amyloliquefaciens SDF-005 for 9 days [ 39 ], Verticillium dahliae VdSHZ-9 grown on PDA with Bacillus N-4 for 7 days [ 40 ], and Fusarium oxysporum grown on PDA with B. subtilis HSY21 for 2 and 3 days [ 29 ]. RNA was also analyzed for Sclerotinia sclerotiorum 1980 grown on PDA containing 10% culture filtrate of B. amyloliquefaciens Bam22 for 1 day [ 41 ], and Botrytis cinerea strain B05.10 grown in PDB with B. subtilis MBI 600 culture filtrate for 0, 24, 48, and 72 h [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was down-regulation of one 1,3-beta-glucan synthase and three 1,3-beta-glucanosyltransferase genes at 4 and 16 h. Note that 1,3-Beta-glucan synthase is a glucosyltransferase that generates beta-glucan, a major component of fungal cell walls, and 1,3-beta-glucanosyltransferase is involved in the elongation of 1,3-beta-glucan [ 43 ]. For both S. sclerotiorum and V. dahilae with Bacillus , 1,3-beta-glucan synthase DEGs were up-regulated [ 40 , 41 ]. It was concluded that this was an attempt to alleviate cell wall damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations